Short Communication: Immunostimulatory effect of tempoyak (fermented durian) on inducing cytokine production (IL-6 and TNF-?) by RAW 264.7 cells - SULVANIA SUSANTO; ANTON SUMARPO; ARLI ADITYA PARIKESIT; AGUS BUDIAWAN NARO PUTRA; ERI ISHIDA; KAHO TABUCH; TAKUYA SUGAHARA (Society for Indonesian Biodiversity, 2018)
Susanto S, Sumarpo A, Parikesit AA, Putra ABNN, Ishida E, Tabuchi K, Sugahara T. 2018. Short Communication: Immunostimulatory effect of tempoyak (fermented durian) on inducing cytokine production (IL-6 and TNF-?) by RAW 264.7 cells. Biodiversitas 19: 318-322. Indonesia is known to be home to various fermented foods with many-reported usage as potential sources of probiotics. Tempoyak (fermented durian) is among one of the Indonesian fermented foods that are rarely studied for its bioactivities. This study was conducted to evaluate the potential bioactivities of tempoyak, particularly the immunostimulatory aspects. Water extract of tempoyak was prepared by suspending the freeze-dried tempoyak sample in distilled water. Immunostimulatory activity of tempoyak water extract was evaluated using mouse macrophage cell line RAW 264.7. ELISA was used to screen cytokine productions (IL-6 and TNF-?) by RAW 264.7 cells following treatment with tempoyak water extract. In addition, real-time RT-PCR was also used to determine IL-6 and TNF-? mRNA expression. We showed that water extract of tempoyak exerts immunostimulatory effects towards RAW 264.7 cells. This was observed from the increased production of IL-6 and TNF-? in a dose-dependent manner. This was also supported by increased IL-6 and TNF-? mRNA expression. Our finding suggests that tempoyak has immunostimulatory effects towards murine macrophage cell line RAW 264.7. However, further studies are needed to identify the specific compounds responsible for inducing immunostimulatory effects.